A Comprehensive Review of Midrange Wireless Power Transfer Using Dielectric Resonators - Azuwa Ali; Mohd Najib Mohd Yasin; Wan Fahmin Faiz Wan Ali; Norsuria Mahmed; Muhammad Ramlee Kamarudin; Ismahayati Adam; Muzammil Jusoh; Hasliza Abdul Rahim; Shing Fhan Khor; Nurulazlina Ramli; Norshamsuri Ali (International Journal of Antennas and Propagation)
Magnetic resonant coupling (MRC) is one of the techniques that are widely used in wireless power transfer (WPT) systems. The technique is commonly used for enhancing distance while maintaining power transfer efficiency (PTE). Many studies have investigated new technologies to extend the distance of MRC while maintaining high PTE values. The most promising technique to date in MRC is the addition of a resonator between the transmitter and the receiver coil. The implementation of the resonator varies based on different designs, sizes, and material types, although the outcomes remain unsatisfactory. By introducing dielectric material resonators, PTE can be improved by lowering the ohmic loss which becomes a problem on conventional resonators. This study presents a general overview on the use of dielectric material as a resonator in MRC WPT technology and its technological development. The basic operation of MRC WPT is summarized with up-to-date technical improvements related to dielectric material as a resonator in the field of WPT. An overview of the current limitations and challenges of this technique is also highlighted in this study.